Gen Z’s Response to Zakiah Daradjat’s Views on Women’s Roles in the Family - Wardani, Azmi Putri Ayu; Istiadah, Istiadah; Arifin, Syamsul (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2025)
The increasing attention to family dynamics amid rising divorce rates in Indonesia underscores the need to examine the roles of women within the household. Drawing on Zakiah Daradjat’s influential work, Islam dan Peranan Wanita (1987), this study examines how Generation Z readers interpret her discourse on the roles of women as wives and mothers. This qualitative study used a reader-response approach with data from 44 purposively selected Gen Z respondents via Google Forms. Conducted in August-September 2024, responses were thematically analyzed using interpretive analysis grounded in hermeneutics, highlighting how personal experiences shaped interpretations of Zakiah Darajat’s views on women’s family roles. The findings indicate that most participants affirmed Daradjat’s views, particularly the centrality of women in fostering family well-being. However, some respondents, particularly unmarried and highly educated participants, expressed more egalitarian perspectives, emphasizing the need for shared responsibility between spouses. The emphasis on women's roles in the family is aligned with the focus of the study, without disregarding the roles of other parties in the dynamics of family life. This study offers insight into family issues that frequently result in disarray between its members, particularly between father and mother or husband and wife, from a range of viewpoints with a diversity of experiences. This study is expected to address the challenges of family life, particularly for women, who often face debates concerning their roles